SISTEM PENGONTROLAN SUHU DAN PH AIR DENGAN KONTROL LOGIKA FUZZY BERBASIS ARDUINO PADA PERANGKAT SMART AKUARIUM UNTUK IKAN MAS KOKI - M Naufal Bariz Abdullah; Mochammad Rusli; Goegoes Dwi Nusantoro (Jurnal Mahasiswa TEUB, 2023)
This study aims to realize a system of controlling the degree of acidity of water and temperature of aquarium water in goldfish using fuzzy logic control so that it is expected to be able to produce healthy and good quality fish. The input data consists of pH and temperature while the output water flow debit is discharged by DC water pumps and heaters.There are pH and temperature sensors that each read every 1.5 seconds with fuzzy output discharge cycles every 1 minute. The design was carried out by the Sugeno method. Based on the test data, 315 data were obtained within 10 minutes, where the system was able to reach the setpoint value when it was in the 292th data, with a time of 8 minutes 47 seconds. The next data of the system runs in steady state. As for steady state errors of 1,05%. Keywords: Fuzzy logic control, Sugeno method, DC water pump, heater, pH sensor, temperature sensor, goldfish.